Appraisal of Cluster Front Line Demonstration on Rapeseed and Mustard in Bihar and Jharkhand (Indian Journal of Extension Education, 2021)
Performance of ten varieties of rapeseed and mustard were assessed through cluster front line demonstration (CFLD) under different agro-climatic condition of Bihar and Jharkhand continuously for four years (2017-18 to 2020-21) by the KVKs of Bihar and Jharkhand. Among the agro-climatic zones of Bihar, highest yield was recorded in the demonstrated plot from zone III (B) i.e. South-West alluvial plain in case of variety RH 0749 (15.29 q/ha) and in Jharkhand state from zone I (Central and North astern plateau) with variety NRCHB 101 (13.31 q/ha). Lowest technology index was observed for variety Rajendra Sufalam in all the zone (-4.96, 5.53, 7.18 and 22.92 % in zone I, III (B), III (A) & II) of Bihar and NRCHB 101 (23.15% in zone I) in Jharkhand. The range of extension gap was1.38 to 4.37 and 1.13 to 4.86 q/ha under the agro-climatic zone of Bihar and Jharkhand, respectively. Pooled data shows that in Bihar, maximum net return (Rs. 46986 /ha) was obtained in variety Rajendra Sufalam in agro-climatic zone III A of Bihar with benefit cost ratio 3.85:1 whereas under agro-climatic condition of Jharkhand maximum net return (Rs. 39598 /ha) was recoded from variety NRCHB 101 with benefit cost ratio 2.80:1.